City in Global Conversations: A Constructivist Study of Jakarta's Para-Diplomacy and Regional Leader's International Visibility - Luerdi Luerdi; Arie Fitria (Lampung Center for Global Studies (LCGS), 2023)
Para-diplomacy has been the agenda of many mega-cities and through which they can express their capacity as well as creativity to pursue specific interests beyond borders. For cities, para-diplomacy can be conducted in many forms starting from merely ceremonial activities to the transnational municipal networks (TMNs). The city active engagement in global forums which mostly belong to the TMNs’ agenda is often associated with the regional leader’s international visibility in global conversations. This paper aims to explain the determinant driving the regional leader’s international visibility within para-diplomacy practice, choosing Jakarta as a case study. This research applied the qualitative method and constructivist approach to investigate the role of ideational factor. The research found that the idea of global city embraced by the regional leader – constructing the city’s identity and interests – encouraged the leader to be active in global forums. The city’s international visibility which was represented by the leader paved Jakarta to be an active global city and through which it would be able to promote its local development and enhance its global role in responding to global issues. This paper suggests that the internal determinants like the regional leaders (governor, mayor) with certain values matter to direct city para-diplomacy whether to project its leadership or merely to prioritize its bilateral para-diplomacy.